Pelatihan Akuntansi Pesantren "Penguatan Kapasitas SDM Pengelola Keuangan Pesantren pada Wilayah Luwu Raya" - Muh Abdi Iman; Andi Nurrahmah Gaffar; Tadjuddin; Zainuddin S; Arzal Syah; Nurfadilah; Hardianti Yusuf; Jibria Ratna Sari; Umar; Muhammad Ikram.S (Room of Civil Society Development, 2023)
Islamic boarding school financial managers must have sufficient knowledge regarding Islamic boarding school accounting which includes procedures for recording financial transactions up to making Islamic boarding school financial reports. Based on the survey results, there are still many Islamic boarding school financial managers who do not understand Islamic boarding school accounting. Lack of training is one of the reasons. So , Islamic boarding school financial managers really need to be given training related to Islamic boarding school accounting . This activity aims to add knowledge to Islamic boarding school financial managers regarding how to record financial transactions and arrive at ways of making financial reports that are correct and in accordance with applicable regulations. Participants in this training activity were attended by eighteen financial managers from nine Islamic boarding schools spread across the Luwu Raya area. The stages of this activity started with preparation, opening, training, practice on how to journalize and make Islamic boarding school financial reports, question and answer discussions, closing and group photos. This activity was carried out smoothly and successfully. Islamic boarding school financial managers in the Luwu Raya region understand Islamic boarding school accounting by being able to properly record financial transactions (journalizing) and understand how to prepare Islamic boarding school financial reports. The conclusion from the results of this community service activity shows that there is a better understanding of Islamic boarding school financial managers in the Luwu Raya area regarding Islamic boarding school accounting (how to record financial transactions and how to prepare Islamic boarding school financial reports).